THE TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN FACING THE CHALLENGES OF GLOBALIZATION - Dani Taupan Ramdani; Khaeruman Khaeruman; Irma Nurmala Dewi (Yayasan Education and Social Center, 2023)
Globalization has brought about significant transformations that have fundamentally altered the business and organizational environment. In the present context, Human Resource Management (HRM) is situated in an important position, confronted with the imperative to adjust and get transformation to sustain its relevance and efficacy. This study aims to examine the evolution of HR Management in response to the demands of globalization, specifically by analyzing the strategies employed to enhance the calibre of HR. Through the methodology of a literature review, this study investigates how the traditional idea of HR Management has been affected by the alterations that have occurred in the global business environment. These findings provide in-depth insights into organisations' strategies to improve HR quality. This research indicates that HR Management requires a transformation to adapt to the era of globalization. This transformation must involve some strategic steps. First, adjusting one's values and culture to those of international business is essential. Second, cultivating the ability to work across cultural boundaries becomes the foundation for international cooperation. Third, there is an emphasis placed on the development of global leadership to ensure the existence of leaders who can successfully manage diversity and complexity. In the fourth place, increased digital competence is incorporated to meet the technological challenges of an increasingly connected work world